Lingmao Formula Combined with Entecavir for HBeAg-Positive Chronic Hepatitis B Patients with Mildly Elevated Alanine Aminotransferase: A Multicenter, Randomized, Double-Blind, Placebo-Controlled Trial. (24th August 2013) - Zhu, Xiao-Jun; Sun, Xue-Hua; Zhou, Zheng-Hua; Liu, Shun-Qing; Lv, Hua; Li, Man; Li, Lu; Gao, Yue-Qiu
Abstract : Objective . To determine the efficacy and safety of Lingmao Formula combined with entecavir for HBeAg-positive chronic hepatitis B patients with mildly elevated alanine aminotransferase (ALT). Methods . 301 patients were randomly assigned to receive Lingmao Formula combined with entecavir (treatment group) or placebo combined with entecavir (control group) for 52 weeks. The outcomes of interest included the reduction of serum HBV DNA level, HBeAg loss, HBeAg seroconversion, ALT normalization, and histological improvement. Results . The mean decrease of serum HBV DNA level from baseline and the percentage of patients who had reduction in serum HBV DNA level ≥2 lg copies/mL in treatment group were significantly greater than that in control group (5.5 versus 5.4 lg copies/mL, P = 0.010 ; 98.5% versus 92.6%, P = 0.019 ). The percentage of HBeAg loss in treatment group was 22.8%, which was much higher than a percentage of 12.6% in control group (P = 0.038 ). There was no significant difference between the two groups in histological improvement. Safety was similar in the two groups. Conclusions . The combination of Lingmao Formula with entecavir could result in significant decrease of serum HBV DNA and increase of HBeAg loss for HBeAg-positive chronic hepatitis B patients with mildly elevated ALT without any serious adverse events. Clinical trial registration number is ChiCTR-TRC-09000594 .